Umuahia Cattle Industry and the Organization of the Cattle Market and Trade, 1914-2000 (Global Journal of Human-Social Science, 2014)
The cattle trade or industry had since the establishment of the cattle market served as one of the most significant economic activities in Umuahia which served the entire Southern Provinces. The Umuahia cattle market within a short period of its establishment had become the distributing centre for the subregion. Cattle trade gained prominence in this town since before the inception of colonialism. The colonial regime took advantage of this trade to serve as a revenue generating industry. The organization of the cattle market was such that took care of various aspects of the trade; the most important aspect of the trade being the credit and credit recovery system. The network that was created as a result of this trade connected various towns and villages within and outside the Southern Provinces. We have employed various sources in this investigation such as oral, archival and written. We discovered that the cattle trade in this area served as one of the most important economic activity of the people. The cattle market became a Mecca of some sort for many other traders such as Kola nut traders, YanKoli traders and other petty trading. The need for the development of the cattle trade stems from the need of the people of the area for beef. That is to say it developed as a result of existence of the market for beef. The cattle market became the first point of contact between the cattle trading community and the people of the Southern Provinces. The importance of the cattle market and trade reached the most remote part of the Southern Provinces.